INFLUENCE OF POST-IMMEDIATE DENTIN SEALING SURFACE TREATMENT ON SHEAR BOND STRENGHT OF LITHIUM DISILICATE - Satria, Angga Novendra Eka; Untara, Tri Endra; Widyastuti, Andina (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Immediate Dentin Sealing (IDS) is a conservative procedure performed to protect the exposed dentin surface after tooth preparation, especially for indirect restorations. Indirect restorations are a common procedure in dentistry for replacing the crown structure of teeth, including various types such as jacket crowns, bridge prostheses, endo crowns, inlays, and veneers. The tooth preparation process can expose dentin tubules, which can trigger pulp tissue irritation and the risk of infection, as well as interfere with the adhesion of the final restoration. Post-IDS surface treatment methods can help enhance the bonding strength. The research aims to investigate the influence of different post-IDS surface treatment on the shear bond strength of lithium disilicate.The study involved 30 upper premolar teeth, divided into three groups. After crown portion buccal surface preparation, all samples underwent IDS, followed by immersion in water and 24-hour incubation. Subsequently, each group received a specific surface treatment: Group I with nylon brush, Group II with nylon brush + pumice, and Group III with sandblasting using aluminum oxide. Lithium disilicate was then cemented on all samples, followed by another 24-hour incubation before shear bond strength testing. Shear bond strength values in MegaPascals (MPa) were analyzed using one-way ANOVA and post hoc Games-Howell tests with a 95% confidence level.The statistical analysis revealed a significant influence of the different treatment groups on shear bond strength (p < 0.05). In conclusion, this study demonstrates a significant impact of varying post-IDS surface treatments on the shear bond strength of lithium disilicate.